(untitled) - Dietrich, J. Kimball (Englewood Cliffs, New Jersey, 1996)
The book is organized into five parts.Part 1 provides an overview of the firms and markets in the financial services industry, and delineates the way these institutions currently fit into the international economy. Part 2 examines each of the six basic financial services in terms of how value is produced for those who demand these services. Part 3 examines the environment within which financial services firms operate and assesses the determinants of the risk and return opportunities confronting managers. Part 4 introduces methods udes to deal with risk in financial strategies. Part 5 reviews the strategic issues relevant to intermediate and long-term planning and introduces the financial methods used to forecast and project future performance
Keywords: Financial institution,Financial services industry; Management